Effect of a Local Food–Based Nutrition Intervention Using Moringa oleifera and Arachis hypogaea on Mid–Upper Arm Circumference among Pregnant Women with Chronic Energy Deficiency: A Quasi-Experimental Study - Hernawati, Erni; Yulianti, Novita; Hidayati, Sofa Nurul (Chakra Brahmanda Lentera Institute, 2026)
Background: Chronic energy deficiency (CED) among pregnant women remains a persistent public health problem in low- and middle-income countries, including Indonesia. Various nutrition programs have been implemented; however, evidence on practical, locally based food interventions—particularly those combining moringa leaves and peanuts in ready-to-consume cookie form—remains limited. This study addresses this gap by evaluating a combined local food–based intervention aimed at improving maternal nutritional status. Methods: his study used a quasi-experimental design with a non-randomized control group and a pretest–posttest approach, reported according to the TREND guideline. The sample consisted of 100 pregnant women with chronic energy deficiency recruited through consecutive sampling at a primary healthcare center. Inclusion criteria were gestational age 12–28 weeks and MUAC < 23.5 cm, while women with pregnancy complications, chronic diseases, food allergies, or multiple pregnancies were excluded. MUAC was measured using a standard non-stretchable tape by trained midwives. The intervention group received moringa leaf and peanut cookies daily for two weeks in addition to standard antenatal care, while the control group received standard care only. Data were analyzed using paired and independent t-tests, and effect size was calculated using Cohen’s d. Results: Both groups showed significant improvements in MUAC after the intervention period (p < 0.001). However, the intervention group demonstrated a greater mean increase in MUAC compared with the control group, with a moderate-to-large effect size (Cohen’s d), indicating not only statistical significance but also meaningful clinical improvement. The effect size was moderate-to-large (Cohen's d = 0.65). Conclusion: The findings indicate that a combined local food–based cookie intervention using moringa leaves and peanuts is more effective than standard antenatal care alone in improving MUAC among pregnant women with CED. This approach supports the integration of culturally appropriate, locally available food interventions into primary healthcare nutrition programs, particularly in low-resource settings.